Dynamic System Coupling in Voice Production - Herbst, Christian T; Elemans, Coen P H; Tokuda, Isao T; Chatziioannou, Vasileios; Švec, Jan G (Journal of voice, 2025)
Voice is a major means of communication for humans, non-human mammals and many other vertebrates like birds and anurans. The physical and physiological principles of voice production are described by two theories: the MyoElastic-AeroDynamic (MEAD) theory and the Source-Filter Theory (SFT). While MEAD employs a multiphysics approach to understand the motor control and dynamics of self-sustained vibration of vocal folds or analogous tissues, SFT predominantly uses acoustics to understand spectral changes of the source via linear propagation through the vocal tract. Because the two theories focus on different aspects of voice production, they are often applied distinctly in specific areas of science and engineering. Here, we argue that the MEAD and the SFT are linked integral aspects of a holistic theory of voice production, describing a dynamically coupled system. The aim of this manuscript is to provide a comprehensive review of both the MEAD and the source-filter theory with its nonlinear extension, the latter of which suggests a number of conceptual similarities to sound production in brass instruments. We discuss the application of both theories to voice production of humans as well as of animals. An appraisal of voice production in the light of non-linear dynamics supports the notion that it can be best described with a systems view, considering coupled systems rather than isolated contributions of individual sub-systems.
Keywords: Source-filter interactions; biomechanika; Vibration; Nonlinear Dynamics; kvalita hlasu; hlasové řasy; akustika řeči; Elasticity; nelineární dynamika; vokalizace zvířat; Biomechanical Phenomena; Speech Acoustics; Voice; MEAD; Voice Quality; Models, Biological; pružnost; zvířata; Humans; biologické modely; vibrace; akustika; Acoustics; Phonation; fonace; Source-filter coupling; Source-filter theory; Myoelastic-aerodynamic theory; Vocal Cords; Vocalization, Animal; lidé; Animals